PERSEPSI ULAMA MUHAMMADIYAH KALIMANTAN TENGAH TERHADAP PENGAKUAN KAWIN BELUM TERCATAT: (Rekognisi Fatwa Majelis Tarjih Tentang Pencatatan Nikah) - Wahdini, Muhammad; Norcahyono, Norcahyono (IAI Darussalam, 2022)
This paper aims to analyze two key variables between the policy of acknowledging marriages that have not been recorded by the Dukapil and the fatwa of the Muhammadiyah Tarjih Council through the perceptions of Muhammadiyah scholars in Palangkaraya City. The type of field research is that researchers conduct direct interviews with careful objects with a phenomenological approach. The results of this study indicate that several sources chose to look at different spaces for the case of unregistered marriage, there is a condition that non-sirri marriage is done intentionally. So it is not absolutely forbidden to marry siri. Regarding the Dukcapil policy, Muhammadiyah Ulama see the positive side with the intention to accommodate and provide administrative convenience to the perpetrators of unregistered marriages who may not know the obligation to register marriages. However, it is certain that the Dukcapil must pay attention to the provisions of the Marriage Law in order to create harmonization between policies. The Muhammadiyah cleric of Palangkaraya city has the principle of Maslahah in this case.